Sectoral Transformation of Turkish Free Zones - (:unkn) unknown (BILGESEL YAYINCILIK SAN & TIC LTD, 2011)
Free zones (FZs) have been used to promote export-orientation of Turkey after 1980. These zones initially focused on labour and resource-intensive manufacturing goods. In time, sectoral diversification took place accompanying the deepening industrialization in the country This paper examines the sectoral restructuring of Turkish FZs. The analysis shows that Turkish zones have supported domestic accumulation via mainly the provision of cheaper foreign inputs to Turkey Besides, the zones have served to global opening-up of Turkish capital by containing export-oriented production. In terms of sectoral transformation, the analysis finds that medium-tech industries dominate Turkish FZs rather than low-tech industries. Moreover high-tech industries have a rising importance in the FZ exports. These findings indicate that the zones have been integrated to Turkey's new industry policies which aim a higher share of medium- and high-tech industries in Turkish manufacturing production and export.
Keywords: Free zones; Export processing zones; Turkish economy; sectoral diversification